HUBUNGAN PENGETAHUAN ORANG TUA TENTANG MAKANAN JAJANAN DENGAN KEJADIAN DIARE PADA ANAK SD NEGERI 1 BUAYAN KECAMATAN BUAYAN KABUPATEN KEBUMEN - Ernawati, E; Maryani, Asih (Jurnal Ilmiah Kesehatan Keperawatan, 2016)
Snack foods that are less qualified health and nutrition will threaten the health of school-age children as gastrointestinal diseases, one of which is diarrhea.This study aims to determine the relationship of parental knowledge about street food with the incidence of diarrhea in children SD Negeri 1 Buayan District of Kebumen.This study uses descriptive correlative with retrospective approach. The study population 192 respondents. The research sample 66 respondents. This study was conducted in February-March 2016. The samples were taken using simple random sampling technique. Analysis of data using the Kolmogorov-Smirnov correlation test with significance level of 0.05. Based on the research results, the majority of parental knowledge about good hawker food as much as 53 (80.3%) of respondents and elementary school children who are not suffering from diarrhea were 58 (87.9%) persons. The results of the analysis with the Kolmogorov-Smirnov can be known p-value of 0.008 with (p <0.05) so that there is a significant relationship between parental knowledge about street food with the incidence of diarrhea in children SD Negeri 1 Buayan District of Kebumen.There is a relationship between parental knowledge about street food with the incidence of diarrhea in children SD Negeri 1 Buayan District of Kebumen.Â Keywords: Diarrhea, Food Snacks, Knowledge